Children’s spontaneous emotional expressions while receiving (un)wanted prizes in the presence of peers - Visser, Mandy; Krahmer, Emiel; Swerts, Marc (Frontiers in Psychology, 2015)
Although current emotion theories emphasize the importance of contextual factors for emotional expressive behavior, developmental studies that examine such factors are currently thin on the ground. In this research, we studied the course of emotional expressions of 8- and 11-year-old children after winning a (large) first prize or a (substantially smaller) consolation prize, while playing a game competing against the computer or a physically co-present peer. We analyzed their emotional reactions by conducting two perception tests in which participants rated children’s level of happiness. Results showed that co-presence positively affected children’s happiness only when receiving the first prize. Moreover, for children who were in the presence of a peer, we found that eye contact affected children’s expressions of happiness, but that the effect was different for different age groups: 8-year-old children were negatively affected, and 11-year-old children positively. Overall, we can conclude that as children grow older and their social awareness increases, the presence of a peer affects their nonverbal expressions, regardless of their appreciation of their prize.